Complement inhibitor of C5 activation from the soft tick Ornithodoros moubata. - Nunn, M; Sharma, A; Paesen, G; Adamson, S; Lissina, O; Willis, A; Nuttall, P (2005)
Blood-feeding ticks must control C activation or be damaged by the host inflammatory response. We report the characterization and expression of a novel, relatively small, broad-acting C inhibitory protein (termed OmCI) from the soft tick Ornithodoros moubata. The native 17-kDa nonglycosylated protein inhibits both human and guinea pig classical and alternative C activation pathways. The IC50 values for each pathway were 12 and 27 nM, respectively, in hemolytic assays using human serum diluted 40-fold. The cDNA encodes a protein of 168 aa, including an 18-aa secretion signal sequence that is absent in the mature form. The inhibitor has 46% amino acid identity with moubatin, a platelet aggregation inhibitor also from O. moubata that is an outlying member of the lipocalin family. Native OmCI had no inhibitory effect on the addition of C8 and C9 to preformed C5b-C7 and C5b-C8 to form the membrane attack complex and no effect on the rate of C3a production by the C3 convertase enzymes C4bC2a, C3(H2O)Bb, or C3bBb. Both recombinant and native OmCI abolish production of C5a by human classical (C4bC3bC2a) and alternative (C3bC3bBb) C5 convertases. Addition of excess C5 but not C3 competes away the inhibitory activity of OmCI, indicating that OmCI targets C5 itself rather than inhibiting the C5 convertase C4bC3bC2a itself. Direct binding of OmCI to C5 was demonstrated by Western blotting and gel filtration chromatography using 125I-labeled proteins. OmCI is the first lipocalin family member shown to inhibit C and also the first natural inhibitor that specifically targets the C5 activation step.